2022
DOI: 10.1021/acscatal.1c05780
|View full text |Cite
|
Sign up to set email alerts
|

Light-Promoted Dearomative Cross-Coupling of Heteroarenium Salts and Aryl Iodides via Nickel Catalysis

Abstract: Partially saturated nitrogen heterocycles are versatile building blocks for the preparation of other nitrogen heterocycles. For example, dihydropyridines can be converted to pyridines, tetrahydropyridines, and piperidines through oxidation, reduction, and functionalization reactions, respectively. Dearomatization of heteroarenes is an attractive approach for the synthesis of partially saturated heterocycles such as dihydropyridines due to the wide availability of heteroarenes. Significant research efforts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…As bidentate and tridentate nitrogenous ligands are the most commonly used in modern variants of Ni-catalyzed coupling reactions of aryl electrophiles, we selected representative achiral examples 39 for evaluation, including bipyridine (BPy)-, 15,16,40−44 phenanthroline (Phen)-, 17,24,45−47 terpyridine (Terpy)-, 48−50 and 2,6-bis((1H-pyrazol-1-yl)methyl)pyridine (BPP)-type ligands. 51,52 We began our study by conducting cyclic voltammetry (CV) measurements of the Ni(II)/Ni(I) redox couple of prepared Ni(II) complexes containing BPy, Phen, Terpy, and BPP ligands. However, Ni complexes bearing the parent bidentate ligands, bipyridine, and phenanthroline resulted in uninterpretable CVs with overlapping peak responses, consistent with literature precedent.…”
Section: Electroanalytical Studies Of the Ni(i) Complexes Andmentioning
confidence: 99%
See 1 more Smart Citation
“…As bidentate and tridentate nitrogenous ligands are the most commonly used in modern variants of Ni-catalyzed coupling reactions of aryl electrophiles, we selected representative achiral examples 39 for evaluation, including bipyridine (BPy)-, 15,16,40−44 phenanthroline (Phen)-, 17,24,45−47 terpyridine (Terpy)-, 48−50 and 2,6-bis((1H-pyrazol-1-yl)methyl)pyridine (BPP)-type ligands. 51,52 We began our study by conducting cyclic voltammetry (CV) measurements of the Ni(II)/Ni(I) redox couple of prepared Ni(II) complexes containing BPy, Phen, Terpy, and BPP ligands. However, Ni complexes bearing the parent bidentate ligands, bipyridine, and phenanthroline resulted in uninterpretable CVs with overlapping peak responses, consistent with literature precedent.…”
Section: Electroanalytical Studies Of the Ni(i) Complexes Andmentioning
confidence: 99%
“…We selected a Ni(BPP)catalyzed cross-coupling reaction between pyridinium salts and aryl iodides, reported by Karimov et al, as a case study. 52 This reaction was analyzed for two reasons: first, it is proposed to proceed via a Ni(I) oxidative addition to aryl iodides and, second, because the reported substrate scope includes reaction yields ranging from 14 to 85% that would potentially enable statistical modeling. Indeed, using MLR, we found that the yields of this reaction correlated with predicted oxidative addition rates (k pred ) and the buried volume of the aryl iodide substrate (% VBur 2.0 ) (Figure 7B).…”
Section: Interrogation Of Mechanisms Through Statistical Modelingmentioning
confidence: 99%
“…40,[51][52][53][54][55][56][57][58][59][60] The introduction of transition metal catalysis via selectively activating the corresponding electrophiles or stabilizing certain intermediates can effectively improve the yields and selectivity of reductive coupling reactions. [61][62][63][64][65][66][67][68] Semmelhack, Kende, and Kumada demonstrated the ability of Ni to mediate the reductive homocoupling of C(sp 2 ) halide electrophiles to construct biaryl products (Scheme 2(a)). [69][70][71] Many new reactions have been discovered based on different kinds of transition-metal insertions into various C-X (X: F, Cl, Br, I, OTf, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Dearomatization of nitrogen heteroarenes for the synthesis of saturated azaheterocycles is an attractive approach as it uses commonly available heteroarenes as starting materials and the reaction products, dihydropyridines, can be further functionalized for the synthesis of pyridines, tetrahydropyridines, and piperidines. The addition of various nucleophiles has been achieved, including asymmetric additions for the synthesis of enantiopure dihydropyridines. With regard to asymmetric dearomative arylation of pyridiniums and related heteroarenium salts, recently our group and others have reported that N -alkyl- and N -acylpyridinium salts can undergo asymmetric dearomatization using aryl boronic acids, aryl zinc, and electron rich aryl nucleophiles. ,,,, …”
mentioning
confidence: 99%